2013
DOI: 10.5194/tc-7-537-2013
|View full text |Cite
|
Sign up to set email alerts
|

Boreal and temperate snow cover variations induced by black carbon emissions in the middle of the 21st century

Abstract: Abstract. We used a coupled climate-chemistry model to quantify the impacts of aerosols on snow cover north of 30 • N both for the present-day and for the middle of the 21st century. Black carbon (BC) deposition over continents induces a reduction in the mean number of days with snow at the surface (MNDWS) that ranges from 0 to 10 days over large areas of Eurasia and Northern America for the presentday relative to the pre-industrial period. This is mainly due to BC deposition during the spring, a period of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…All the experiments were conducted with the present-day global aerosol emission inventory described in Lamarque et al (2009), a decadal resolved inventory made for the Coupled Model Inter-comparison Project Phase 5 (CMIP5, CLI-VAR special issue, 2011). We further used the detailed representation of snow cover implemented in ORCHIDEE by Krinner et al (2006) and used in Ménégoz et al (2013a). This includes a two-layer scheme describing the snow albedo as a function of snow grain size and aerosol content in the snow based on Wiscombe and Warren (1980).…”
Section: The Lmdz-orchidee-inca Climate Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…All the experiments were conducted with the present-day global aerosol emission inventory described in Lamarque et al (2009), a decadal resolved inventory made for the Coupled Model Inter-comparison Project Phase 5 (CMIP5, CLI-VAR special issue, 2011). We further used the detailed representation of snow cover implemented in ORCHIDEE by Krinner et al (2006) and used in Ménégoz et al (2013a). This includes a two-layer scheme describing the snow albedo as a function of snow grain size and aerosol content in the snow based on Wiscombe and Warren (1980).…”
Section: The Lmdz-orchidee-inca Climate Modelmentioning
confidence: 99%
“…Anthropogenic BC deposited on snow was found to shorten the current duration of the snow cover season in the Northern Hemisphere by several days (Ménégoz et al, 2013a) and to contribute to the significant decrease of the snow cover extent observed during the last decades (Dery et al, 2007). Brutel-Vuilmet et al (2013) found the new generation of global climate model to correctly simulate the present-day snow cover extent, but to underestimate its decrease over the last decades.…”
mentioning
confidence: 99%
“…• A widely expected consequence of climate warming at boreal latitudes is an increase in the frequency and severity of forest wildfires, and these fires have the potential to severely impact the chemistry and radiative balance of the Northern Hemisphere's atmosphere and cryosphere (e.g., Kondo et al, 2011;Ménégoz et al, 2013). The records of biomass burning emissions developed from the Mt.…”
Section: Future Workmentioning
confidence: 99%
“…BC deposited on snow in the Himalayan region induces an increase in net shortwave radiation at the snow surface with an annual mean of about 1 to 3 W m −2 , producing an estimated 0.05-0.3 • C warming (Ménégoz et al, 2014). The deposition of anthropogenic BC has been observed to contribute significantly to the decrease in snow cover extent over recent decades (Déry et al, 2007) and a shortening of the duration of the snow cover season by several days (Ménégoz et al, 2013). The climate warming efficiency of BC in snow is greater than the warming efficiency of other anthropogenic pollutants, including carbon dioxide (Hansen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%